The spatial distribution of coral diversity and conection to the oceanography conditions of Tidore Island Waters - Abdul Motalib Angkotasan; Abdul Ajiz Siolimbona; Salnudin Salnuddin; Firdaut Ismail; Asmar Hi Daud; Nyoman Metta N Natih (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The Optimal coral reefs are distributed in shallow waters between 0 and 30 m deep, influenced by the hydro-oceanographic variability of the waters. Globally, corals are distributed in various forms of water predominantly found in the Coral Triangle region. This study aims to examine the spatial distribution of coral biodiversity in the Tidore Island Waters. This study was conducted in the Tidore Island Waters at three research stations, namely Tugulufa Station, Toloa Station and Tanjun Konde Station. This study analyzed the spatial distribution of coral and the relationship between coral biodiversity and the hydro-oceanographic conditions of the Tidore Island waters. The results showed that the highest coral diversity was found at Toloa Station, with the largest area being the Acropora tabulate coral life form. Acropora coral species were found throughout the research location, with the highest percentage of cover found at Toloa Station. Temperature and salinity variables are the main characteristics in the three research locations. Temperature has a role and main characteristics in Toloa Station. The spatial distribution of Acropora corals is related to temperature and salinity variability.Keywords:Coral reefTidore waterTemperatureSalinity